2020
DOI: 10.1038/s41594-020-0419-3
|View full text |Cite|
|
Sign up to set email alerts
|

SLX4 interacts with RTEL1 to prevent transcription-mediated DNA replication perturbations

Abstract: Back to Main Page1. Please note that only one statement of equally contributing authors is allowed (as well as one statement of joint supervision, if appropriate), so the two present statements have been amalgamated into one for now. If the two pairs of authors need to be diffentiated, a statement can be added to the author contributions section to explain. If you would like to do this, please provide some text to add.The meer fact that two different statements were made was because they were not the same. So … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 80 publications
3
43
0
Order By: Relevance
“…Likewise, POLδ deficiency also renders cells hypersensitive to TOPOI inhibitors (Tumini et al 2016), raising the possibility that both RTEL1 and POLδ play a critical role in overcoming TOPOI-induced DNA damage during replication. In further support of this concept, two reports published at the time of submission of our revised manuscript suggest that RTEL1 is involved in suppressing replication-transcription conflicts (Takedachi et al 2020;Wu et al 2020) and R-loop accumulation (Wu et al 2020).…”
Section: Discussionsupporting
confidence: 53%
“…Likewise, POLδ deficiency also renders cells hypersensitive to TOPOI inhibitors (Tumini et al 2016), raising the possibility that both RTEL1 and POLδ play a critical role in overcoming TOPOI-induced DNA damage during replication. In further support of this concept, two reports published at the time of submission of our revised manuscript suggest that RTEL1 is involved in suppressing replication-transcription conflicts (Takedachi et al 2020;Wu et al 2020) and R-loop accumulation (Wu et al 2020).…”
Section: Discussionsupporting
confidence: 53%
“…In addition to its interaction with the three nucleases, SLX4 also interacts with proteins involved in mismatch repair (MMR; MSH2, MSH3, and MSH6) and telomere maintenance (TRF2, RTEL1, and SLX4IP), as determined by mass spectrometry (Gonzá lez-Prieto et al, 2015;Svendsen et al, 2009;Takedachi et al, 2020;Wu et al, 2020;Zhang et al, 2019). The MSH proteins form two heterodimeric ATPases, MutSa (MSH2-MSH6) and MutSb (MSH2-MSH3), which are key components of the MMR system that removes errors incorporated during DNA replication (Fishel, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TRCs and DNA:RNA hybrids activate the Fanconi anemia (FA) DSB pathway to resolve R-loops [ 60 , 61 ]. In line with this mechanism, a recent study showed that SLX4, a tumor suppressor, directs the recruitment of FANCD2 (a critical FA complex member) to RNA polymerase II, and this action is necessary for prevention of TRCs in unstressed cells [ 62 ]. Polycomb group proteins BMI1 and RNF2 were recently revealed to suppress TRCs as well [ 63 ].…”
Section: Replication Stressmentioning
confidence: 99%